DAMPAK FOOD LOSS AND FOOD WASTE TERHADAP LINGKUNGAN, EKONOMI DAN SOSIAL STUDI KASUS: INDONESIA - Sholihah, Nelies Nur (Jurnal Multidisipliner Kapalamada, 2025)
Food loss and waste (FLW) is a global issue with serious impacts on food security, the environment, and the economy. Indonesia, as the second-largest contributor to FLW in the world, generates 23–48 million tons of FLW per year (2000–2019). This study aims to analyze the causes, conditions, impacts, and policy responses related to FLW in Indonesia using a literature review method and the DPSIR framework (Driving Force, Pressure, State, Impact, Response). The analysis shows that the main driving factors of FLW include population growth, wasteful consumption patterns, inefficiencies in the food supply chain, climate change, and the conversion of agricultural land. The impacts include economic losses of 213–551 trillion rupiahs, loss of nutritional content that could feed millions of people, and a significant contribution to greenhouse gas emissions. Government policy responses, such as Law No. 18/2008 and the Circular Economy initiative, have been implemented but have not yet comprehensively addressed FLW reduction across the supply chain. This study emphasizes the importance of an integrated national strategy to support food security and reduce carbon emissions in achieving the Sustainable Development Goals (SDGs).